2022
DOI: 10.48550/arxiv.2204.14267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Grammar for Hypothesis-Driven Visual Analysis

Abstract: A hallmark of visual analytics is its ability to support users in translating broad, open-ended analytic questions (e.g., "is our company succeeding?") into verifiable hypotheses that can be tested from the available data (e.g., "our total revenue increased this past quarter"). However, the process of converting open-ended analytic questions into testable hypotheses is complex and often ill-defined. Beyond high-level descriptions, the visual analytics literature lacks a formalization that can be operationalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The visual analytics approach helped connect placental gene expression to placental biological processes involving aquaporins and other gene groups. Future studies with the datasets could consider hypothesis-driven analysis of the datasets and grammar-based approaches to a hypothesis-driven theory of visual analytics [94,95]. We generated volcano plots, box plots, enclosure data tables, and heatmaps to visualize the RNA-Seq gene expression data.…”
Section: Discussionmentioning
confidence: 99%
“…The visual analytics approach helped connect placental gene expression to placental biological processes involving aquaporins and other gene groups. Future studies with the datasets could consider hypothesis-driven analysis of the datasets and grammar-based approaches to a hypothesis-driven theory of visual analytics [94,95]. We generated volcano plots, box plots, enclosure data tables, and heatmaps to visualize the RNA-Seq gene expression data.…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated until participants reported they had done all they could with hypothesis generation without performing data exploration or analysis. Turning Open-ended Questions into Formal Hypotheses: To ensure that the participants were forming meaningful analytic questions and hypotheses that could eventually be tested to solve the challenge, the participants were asked to refine any open-ended questions into formalized hypotheses using either the hypothesis grammar by Suh et al [26] or the Hypothesis Quality Scale by Sunal and Haas [27] (see Table 1). An example of this process is discussed in Section 4.3.…”
Section: Tasksmentioning
confidence: 99%
“…This approach of methodologically performing data analysis is inspired by recent work in pre-registering hypotheses before visual analysis [12,26] and experimental designs [4]. In experimental studies, pre-registration can prevent p-hacking [7], HARKing (Hypothesizing After Results are Known) [11], and postdiction (as opposed to prediction) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these tools use the query to retrieve data from domain-specific databases, which differs from our proposed query conversion method for search engines. Moreover, although research has identified other ways to encode visual findings and hypotheses beyond visual query constructors [22], no existing work, as far as the authors know, has demonstrated ways to use such methodology to convert a visual selection into a search query as Q4EDA proposes.…”
Section: Related Workmentioning
confidence: 99%